Praktikal Pelaksanaan Konsep Hisbah Dalam Pentadbiran Audit Syariah Di Bank Islam Malaysia Berhad: Practical Implementation of Hisbah Concepts in Shariah Audit Administration of Bank Islam Malaysia Berhad - Abdul Manaf, Sanusi; Che Pa, Bharuddin (Online Journal of Research in Islamic Studies, 2017)
Shariah audit administration of Islamic Financial Institutions (IFIs) face several challenges when addressing various issues related to the implementation of Shariah compliance. Key issues include auditor qualifications, Shariah compliance in the development and promotion of products and services, and policies for addressing the issue of Shariah non-compliance. Addressing these issues requires consideration of the concept of hisbah in the history of Islamic administration. In relation to this, the primary purpose of this study is an examination of theories of hisbah found in both classical and modern references. The importance of this study is in helping strengthen elements of hisbah to act as a value-added feature of Shariah administrative audit systems in Malaysia. The study found that within the concept of hisbah, elements of muhtasib, muhtasab fih, muhtasab alaih and nafs al-ihtisab are considered in the audit system of Bank Islam Malaysia Berhad (BIMB). It is hoped that the presence of elements of hisbah will lead BIMB to seriously promote a Sharia administrative audit system which correctly carries out the functions of hisbah elements in the context of the hisbah concept.